Measurement of multiphysical material parameters of piezoceramic components for high-power ultrasonic applications - Friesen, Olga; Claes, Leander; Hölscher, Jonas; Henning, Bernd; Scheidemann, Claus; Hemsel, Tobias; Kuess, Raphael; Walther, Andrea; Spieker, Carsten; Förstner, Jens (tm - Technisches Messen)
Simulation-based design of high-power ultrasonic systems depends on the accurate modelling of the electromechanical behaviour of piezoceramic materials. In practical transducer applications, the relevant operating points are influenced by mechanical preload and heating, both of which give rise to changes in the elastic, dielectric, and piezoelectric material properties. Material parameters identified under idealised, unloaded conditions are therefore insufficient to represent piezoceramic material behaviour under realistic operating conditions. To overcome this limitation, experimental setups are developed that enable the measurement of electrical impedance spectra under controlled thermal and mechanical conditions. The acquired impedance data are used in an inverse identification procedure, in which the behaviour of a finite element forward model is iteratively fitted to the measurements using a block coordinate descent optimisation strategy guided by a sensitivity analysis. This yields effective linear material parameters as a function of temperature and mechanical stress at varying operating points. The identified temperature-dependent parameters, for instance, can be employed in a coupled thermo-electromechanical simulation framework to predict the temperature-dependent material behaviour during operation. The linear identification based on varying operation points provides an initial approximation of the nonlinear material response, establishing a basis for the development of corresponding nonlinear material models.
Keywords: tet_topic_piezo

Task-specific scan trajectory modification for dimensional X-ray computed Tomography with high throughput - Butzhammer, Lorenz; Hausotte, Tino (tm - Technisches Messen)
Zusammenfassung Eine Erweiterung der Scantrajektorie für die industrielle Röntgen-Computertomographie von einer kreisförmigen Form (entsprechend einer 360°-Rotation des Messobjekts) hin zu frei wählbaren Aufnahmeposen hat das Potenzial, durch eine geeignete Trajektorienanpassung Messabweichungen zu reduzieren. In diesem Beitrag wird eine solche Trajektorienanpassung durch einen Hexapoden als Messobjektmanipulator und eine güteparameterbasierte Methodik zur Wahl einzelner Trajektorienpunkte erreicht. Die Ergebnisse zeigen, dass sich vor allem für eine geringe Projektionszahl signifikante Vorteile ergeben, was vor allem im Hinblick auf Inline-CT mit hohem Durchsatz von Relevanz ist.

Task-specific scan trajectory modification for dimensional X-ray computed Tomography with high throughput - Butzhammer, Lorenz; Hausotte, Tino (tm - Technisches Messen)

Estimation of piezoelectric material parameters of ring-shaped specimens - Friesen, Olga; Claes, Leander; Feldmann, Nadine; Henning, Bernd (tm - Technisches Messen)
The estimation of accurate piezoelectric material parameters is a fundamental prerequisite for simulation-driven design of piezoelectric actuators and sensors. Previous studies show that a full set of material parameters can be determined in an inverse procedure using a single disc-shaped specimen with an electrode structured for increased sensitivity with respect to all material parameters. However, in the case of high-power actuator applications, ring-shaped piezoelectric components are often employed, necessitating an adaptation of the previously developed method. The alteration in geometry introduces some advantages. Accordingly, there is no longer any requirement to modify the electrode structure in order to enhance sensitivity. The method to estimate the material parameters presented here consists of a total of three stages. An initial, approximate estimation of the material parameters is determined using analytical approximations for the resonance frequencies from the IEEE standard. These values are optimised in an inverse procedure that employs analytic expressions for the electrical impedance of piezoelectric rings as the forward model. Further refinement is achieved by using Finite Element (FE) simulations as the forward model again in an inverse procedure. The method is applied to electrical impedance measurement data, yielding material parameters for hard piezoelectric rings. The result shows a good agreement between the simulation and measurement results, indicating realistic material parameter values.

Vorzeichenrichtige tomographische Rekonstruktion von Ultraschallfeldern mit Hilfe der Schlierentechnik - Hetkämper, Tim; Claes, Leander; Henning, Bernd (tm - Technisches Messen)
Keywords: Electrical and Electronic Engineering; Instrumentation

Über die Abgrenzung von Auflösungskonzepten in der industriellen Computertomografie - Binder, Felix; Hausotte, Tino (tm - Technisches Messen)
Unter dem Begriff der Auflösung wird für gewöhnlich das kleinste messbare Merkmal eines Messsystems verstanden. In der dimensionellen Computertomografie hingegen haben sich in den vergangenen Jahren mehrere Auflösungskonzepte etabliert, die aufgrund der fehlenden Normung zueinander im Kontrast stehen. In diesem Beitrag werden die drei häufigsten Konzepte, die Voxelgröße, die Ortsauflösung und die metrologische Strukturauflösung in Kürze vorgestellt. Anschließend wird eine Abgrenzung zwischen den Konzepten getroffen und ein Integration der bestehenden Konzepte in ein gemeinsames Amplituden-Wellenlängen Diagramm diskutiert.
Keywords: Electrical and Electronic Engineering; Instrumentation

Herausforderungen bei computertomografischen Untersuchungen von Fügeverbindungen - Busch, Matthias; Butzhammer, Lorenz; Hausotte, Tino (tm - Technisches Messen)
Die Erkennbarkeit von Rissen und geometrischen Qualitätskennwerten von Fügeverbindungen mittels Computertomografie ist von der Interfacestrukturauflösung abhängig, welche mittels geeigneter Prüfkörper untersucht wird. Die Reduktion von Abbildungsartefakten im Bereich von Bauteilzwischenräumen und -oberflächen verbessert deren dimensionelle Erfassbarkeit.
Keywords: Electrical and Electronic Engineering; Instrumentation

Lamb wave based approach to the determination of acoustic material parameters - Johannesmann, Sarah; Claes, Leander; Feldmann, Nadine; Zeipert, Henning; Henning, Bernd (tm - Technisches Messen)
Abstract In this paper a measurement procedure to identify viscoelastic material parameters of plate-like samples using broadband ultrasonic waves is presented. Ultrasonic Lamb waves are excited via the thermoelastic effect using laser radiation and detected by a piezoelectric transducer. The resulting measurement data is transformed to yield information about multiple propagating Lamb waves as well as their attenuation. These results are compared to simulation results in an inverse procedure to identify the parameters of an elastic and a viscoelastic material model.
Keywords: Electrical and Electronic Engineering; Instrumentation

Investigating peculiarities of piezoelectric detection methods for acoustic plate waves in material characterisation applications - Claes, Leander; Schmiegel, Hanna; Grünsteidl, Clemens; Johannesmann, Sarah; Webersen, Manuel; Henning, Bernd (tm - Technisches Messen)
Acoustic waves in plates have proven a viable tool for testing and material characterisation purposes. There are a multitude of options for excitation and detection of theses waves, such as optical and piezoelectric systems. While optical systems, with thermoelastic excitation and interferometric detection, have the benefit of being contactless, they usually require rather complex and expensive experimental setups. Piezoelectric systems are more easily realised but require direct contact with the specimen and usually have a limited bandwidth, especially in case of piezoelectric excitation. In this work, the authors compare the properties of piezoelectric and optical detection methods for broad-band acoustic signals. The shape (e. g. the displacement) of a propagating plate wave is given by its frequency and wave number, allowing to investigate correlations between mode shapes and received signal strengths. This is aided by evaluations in normalised frequency and wavenumber space, facilitating comparisons of different specimens. Further, the authors explore possibilities to utilise the specific properties of the detection methods to determine acoustic material parameters.

Modelling damping in piezoceramics: A comparative study - Feldmann, Nadine; Schulze, Veronika; Claes, Leander; Jurgelucks, Benjamin; Meihost, Lars; Walther, Andrea; Henning, Bernd (tm - Technisches Messen)
The progress in numerical methods and simulation tools promotes the use of inverse problems in material characterisation problems. A newly developed procedure can be used to identify the behaviour of piezoceramic discs over a wide frequency range using a single specimen via fitting simulated and measured impedances by optimising the underlying material parameters. Since there is no generally accepted damping model for piezoelectric ceramics, several mechanical damping models are examined for the material identification. Three models have been chosen and their ability to replicate the measured impedances is evaluated. On the one hand, the common Rayleigh model is considered as a reference. On the other hand, a Zener model and a model using complex constants are extended to model the transversely isotropic material. As the Rayleigh model is only valid for a limited frequency range, it fails to model the broadband behaviour of the material. The model using complex constants leads to the best fit over a wide frequency range while at the same time only adding three additional parameters for modelling damping. Thus, damping can be assumed approximately frequency-independent in piezoceramics.

Inverse piezoelectric material parameter characterization using a single disc-shaped specimen - Feldmann, Nadine; Schulze, Veronika; Claes, Leander; Jurgelucks, Benjamin; Walther, Andrea; Henning, Bernd (tm - Technisches Messen)
The increasingly simulation-driven design process of ultrasonic transducers requires several reliable parameters for the description of the material behaviour. Exact results can only be achieved when a single specimen is used in the identification process, which typically is prone to the problem of low sensitivities to certain material parameters and thus high uncertainties. Therefore, a custom electrode topology for increased sensitivity is proposed for a piezoceramic disc. The thereupon conducted measurements of the electric impedance can be used as a starting point for an inverse approach where an equivalent simulation model is used to identify fitting material parameters. An optimisation strategy based on a preliminary sensitivity analysis is presented that leads to a good agreement between measurement and simulation. Furthermore, the proposed measurement procedure is able to evaluate the quality of the simulation model. Hence, different frequency-dependent damping models are presented and evaluated.

Acoustic absorption measurement for the determination of the volume viscosity of pure fluids / Messverfahren für die akustischen Absorption zur Bestimmung der Volumenviskosität reiner Fluide - Claes, Leander; Hülskämper, Lars Moritz; Baumhögger, Elmar; Feldmann, Nadine; Chatwell, René Spencer; Vrabec, Jadran; Henning, Bernd (tm - Technisches Messen)

Uncertainty estimation for linearised inverse problems comparing Bayesian inference and a pseudoinverse approach for acoustic transmission measurements - Feldmann, Nadine; Bause, Fabian; Henning, Bernd (tm - Technisches Messen)